The effect of health on urban-settlement intention of rural-urban migrants in China - Xie Shenghua; Wang Jungling; Chen Juan; Ritakallio Veli-Matti (Elsevier, 2022)
Previous studies have not paid enough attention to the effect of health on urban-settlement intention of rural-urban migrants in China. Using survey data from the Rural Urban Migration in China project, this article examines how self-rated physical and mental health influence rural-urban migrants’ intention to settle down in cities. First, the results show that both self-rated physical and mental health are significant factors influencing the migrants’ intention to permanently move to cities. Second, the effect of physical health on rural-urban migrants’ intentions to permanently reside in cities can be moderated by their length of urban residence. Third, the impact of health on rural-urban migrants’ urban-settlement intention shows no generational differences. According to the research findings, this paper discusses how urban-settlement intention of rural-urban migrants based on health selection might impair urbanization, exacerbate health disparity between the rural and urban areas, and aggravate the burden on healthcare system in rural areas of China in the long run.